Morbidity of Inguinofemoral Lymphadenectomy in Vulval Cancer. (4th January 2012) - Soliman, A. A.; Heubner, M.; Kimmig, R.; Wimberger, P.
Abstract : Background . The aim of this study is to detect possible risk factors for development of short- and long-term local complications after inguinofemoral lymphadenectomy for vulval cancer. Methods . This retrospective cohort study included 34 vulval cancer patients that received inguinofemoral lymphadenectomy. The detected complications were wound cellulitis, wound seroma formation, wound breakdown, wound infection, and limb lymphoedema. Followup of the patient ran up to 84 months after surgery. Results . Within a total of 64 inguinofemoral lymphadenectomies, 24% of the inguinal wounds were affected with cellulitis, 13% developed a seroma, 10% suffered wound breakdown, 5% showed lower limb edema within a month of the operation, and 21.4% showed lower limb edema during the long-term followup. No significant correlation could be found between saphenous vein ligation and the development of any of the local complications. The 3-year survival rate in our cohort was 89.3%. Conclusions . Local complications after inguino-femoral lymphadenectomy are still very high, with no single pre-, intra-, or postoperative factor that could be incriminated. Saphenous vein sparing provided no significant difference in decreasing the rate of local complications. More trials should be done to study the sentinel lymph node detection technique.